Development and psychometric evaluation of the type 2 diabetes nutrition therapy adherence scale - Ulger, Taha Gokmen; Sendur, Elif Gencer; Acik, Murat; Bektas, Murat (Elsevier Sci Ltd, 2026)
Aims: Type 2 diabetes mellitus is a major global public health concern closely associated with unhealthy dietary patterns. Medical nutrition therapy plays a central role in its prevention and management; however, assessing adherence remains challenging. This study aimed to develop and psychometrically evaluate the Type 2 Diabetes Nutrition Therapy Adherence Scale (DNTA-S), a culturally appropriate instrument for assessing adherence to nutrition therapy among individuals with type 2 diabetes. Methods: This methodological and cross-sectional study was conducted with 420 adults diagnosed with type 2 diabetes. Content validity was assessed using the Davis technique based on expert evaluations. Construct validity was examined through exploratory and confirmatory factor analyses. Reliability was evaluated using Cronbach's alpha, split-half, and test-retest analyses. Results: The final 20-item scale consisted of four dimensions. The four-factor structure explained 61.29% of the total variance, with acceptable factor loadings. Confirmatory factor analysis supported the structure and demonstrated good model fit (RMSEA=0.060; CFI=0.943). The overall Cronbach's alpha was 0.915, and subdimension reliability coefficients were within acceptable ranges. Test-retest reliability indicated excellent stability (ICC=0.95). Conclusions: The DNTA-S is a valid and reliable multidimensional instrument that captures key aspects of dietary adherence and may support both clinical practice and research.
Keywords: Type 2 Diabetes; Medical Nutrition Therapy; Adherence; Scale Development; Psychometric Evaluation